2016
DOI: 10.12809/hkmj154710
|View full text |Cite
|
Sign up to set email alerts
|

Sperm retrieval rate and pregnancy rate in infertile couples undergoing in-vitro fertilisation and testicular sperm extraction for non-obstructive azoospermia in Hong Kong

Abstract: Objective: There are currently no local data on the sperm retrieval and pregnancy rates in in-vitro fertilisation and testicular sperm extraction cycles, especially with regard to the presence of genetic abnormalities. This study aimed to determine the sperm retrieval and pregnancy rates in infertile couples who underwent in-vitro fertilisation and testicular sperm extraction for non-obstructive azoospermia.Methods: This retrospective case series was conducted at a tertiary assisted reproduction unit in Hong K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…Five (9.43%) studies used more than one SSR technique. Amongst the 53 papers (Ando et al, 2013;Arafa et al, 2018;Bakircioglu et al, 2011;Brandell et al, 1998;Cetinkaya et al, 2015;Chehrazi et al, 2017;Chen et al, 2019;Choi et al, 2013;Emre Bakircioglu et al, 2006;Ferhi et al, 2009;Franik et al, 2018;Garolla et al, 2018;Goncalves et al, 2017;Greco et al, 2013;Güneri et al, 2016;Hopps et al, 2003;Huang et al, 2020;Ishikawa et al, 2009;Iwatsuki et al, 2017;Kizilkan et al, 2019;Klami et al, 2018;Kleiman et al, 2016;Ko et al, 2016;Koga et al, 2007;Madgar et Okada et al, 2005;Ozer et al, 2018;Ozveri et al, 2015;Park et al, 2013;Pavan-Jukic et al, 2020;Plotton et al, 2015;Pozzi et al, 2020;Ramasamy et al, 2009;Reubinoff et al, 1998;Rohayem et al, 2015;Sabbaghian et al, 2018;Salvarci & Zamani, 2018;Schiff et al, 2005;Schwarzer et al, 2016;Selice et al, 2010;Seo et al, 2004;…”
Section: Search Results and Characteristics Of Studiesunclassified
See 2 more Smart Citations
“…Five (9.43%) studies used more than one SSR technique. Amongst the 53 papers (Ando et al, 2013;Arafa et al, 2018;Bakircioglu et al, 2011;Brandell et al, 1998;Cetinkaya et al, 2015;Chehrazi et al, 2017;Chen et al, 2019;Choi et al, 2013;Emre Bakircioglu et al, 2006;Ferhi et al, 2009;Franik et al, 2018;Garolla et al, 2018;Goncalves et al, 2017;Greco et al, 2013;Güneri et al, 2016;Hopps et al, 2003;Huang et al, 2020;Ishikawa et al, 2009;Iwatsuki et al, 2017;Kizilkan et al, 2019;Klami et al, 2018;Kleiman et al, 2016;Ko et al, 2016;Koga et al, 2007;Madgar et Okada et al, 2005;Ozer et al, 2018;Ozveri et al, 2015;Park et al, 2013;Pavan-Jukic et al, 2020;Plotton et al, 2015;Pozzi et al, 2020;Ramasamy et al, 2009;Reubinoff et al, 1998;Rohayem et al, 2015;Sabbaghian et al, 2018;Salvarci & Zamani, 2018;Schiff et al, 2005;Schwarzer et al, 2016;Selice et al, 2010;Seo et al, 2004;…”
Section: Search Results and Characteristics Of Studiesunclassified
“…Quality assessment of the included studies revealed the majority of studies (n = 37; 69.81%) to be of fair quality scoring a total of 6 stars, while the remaining 16 (30.19%) studies were considered of high quality (8 studies scoring 9 stars (Bakircioglu et al, 2011;Chehrazi et al, 2017;Choi et al, 2013;Ishikawa et al, 2009;Plotton et al, 2015;Tsujimura et al, 2004;Yamaguchi et al, 2020;Zhang et al, 2021) and 8 studies scoring 7 stars (Arafa et al, 2018;Chen et al, 2019;Huang et al, 2020;Iwatsuki et al, 2017;Klami et al, 2018;Kleiman et al, 2016;Ko et al, 2016;Takeda et al, 2017).…”
Section: Search Results and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 In addition, male factor infertility has been associated with reduced life expectancy and heavy financial burden, potentially causing excessive strain within personal relationships of those who suffer from the condition. 5 7 …”
Section: Introductionmentioning
confidence: 99%